Institutionalizing Women's Enterprise Policy: A Legitimacy-Based Perspective. (May 2019) - Arshed, Norin; Chalmers, Dominic; Matthews, Russell
Despite efforts to increase the quantity and quality of women-owned businesses, enterprise policy has enjoyed only modest success. This article explores the role of legitimacy in these outcomes by examining how and when individual stakeholders evaluate and then influence the legitimacy of women's enterprise policy. We draw on 45 interviews with actors in the UK enterprise policy ecosystem and an ethnographic study of the policy process. We present a multilevel model of two opposing legitimacy processes: a legitimacy repair loop and a delegitimizing loop. In doing so, we provide a novel perspective on policy institutionalizing.